The course of professionalization: Jewish nursing in Poland in the interwar period. Issue 1 (March 2019) - Zalashik, Rakefet; Davidovitch, Nadav
Argument: This paper focuses on the Jewish nursing profession in Poland during the interwar period. We argue that the integration of Jewish women in medical activity under the AJDC (American Jewish Distribution Committee) and TOZ (Towarzystwa Ochrony Zdrowia Ludności Żydowskiej [the Society for the Protection of the Health of the Jewish People]) emerged in Poland less from the adoption of gender equality and more out of necessity. On the one hand, JDC and TOZ needed Jewish nurses and public health nurses to carry out their health campaigns and build a public health infrastructure. On the other hand, a new generation of Jewish women needed job opportunities that would enable them to make a living and be independent. More broadly this case study shows that the implementation of American "reformative" ideals into the local Polish reality, including in the newly emerging public health field, involved adaptation, negotiation, and in some cases, resentment.